Tiny house living ideas for building and living well in less than 400 square feet - Mitchell, Ryan (Betterway Home, 2014)
Free yourself from clutter, mortgages and home maintenance while making more room for th important things. Mitchell helps you explore the philosophies behind the tiny house movement, determine whether it's a good fit for you, and transition to a smaller space